In or On? Island Words, Island Worlds: II - Owe Ronström (Island Studies Journal, 2011)
The first part of the paper examines uses and meanings of the orientational metaphors ‘in’, ‘on’, ‘out’ and ‘off’. In the discussed languages in North Western Europe there are general principles of metaphoric entailment and underlying image schemas that guide the choice of positional metaphor: islands you are normally ‘on’, and mainlands ‘in’. The second part of the paper examines cases where this use is debated or contested. The author finds that these contestations seem to be fuelled by the different relations between subject and object that positional metaphors entail. Expressions with ‘in’ highlight belonging and collective identity, enlarge objects by conceptualizing them as encompassing containers, and reduce subjects to a part of the object. Expressions with ‘on’ highlight individuality and agency, reduce the object, and enlarge the subject by placing it above the object. Such differing entailments of positional metaphors may influence how islands are positioned and understood.